The Indispensable Liabilities of Leaders in Times of Covid-19 Pandemic - Ali, Mazhar; Anum, Zarmeena; Nasir, Anam; Ahmad , Nazir (South Asian Journal of Social Sciences and Humanities, 2021)
This explanatory paper seeks to examine domestic and international competences of world  leaders towards the organizations in COVID-19. In this crisis phase, the organization empowers  leader’s critical competences to survive in the crucial business environment. The role of leaders  in this Pandemic ramification is exclusively meticulous. The particular research question that  drives this work is: what leadership skills are needed during crises? And what is it? What are the  critical competences which help their organizations during and post-crisis? In this manuscript,  we have some literature-based descriptions from foreign and domestic perspectives as necessary  competences for leadership activities a worldwide epidemic. We discussed leadership skills  needed in period of disasters, accompanied by discussing best practices leadership in various  ways and new reflections for top management analysts and professionals post a financial crisis. This study highlights and extends a few appropriate leadership qualities and competences which  are highly useful for all the current leaders and organizations.
Keywords: COVID-19; crisis management; leadership competences; critical leader’s qualities